2005
DOI: 10.1258/0951484054572547
|View full text |Cite
|
Sign up to set email alerts
|

The willingness to donate blood: an empirical analysis of socio-demographic and motivation-related determinants

Abstract: Since the willingness to donate blood is not very high among large parts of the population, a better understanding of the determinants for the willingness to donate blood is of significant importance. This article is intended to contribute to higher uniformity of results in the context of research on blood donation behaviour. Exploratory factor analysis non-parametric tests are used to accomplish this. Potentially important socio-demographic and motivation-related variables particularly affecting the willingne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(64 citation statements)
references
References 24 publications
7
52
1
1
Order By: Relevance
“…In a study conducted by Tscheulin and Lindenmeier, they found that the willingness to donate blood does increase with the level of education [15]. A consistent result also was found in a study conducted in the year 2006 that taken from Ahuja and Saluja whereby they found that 76% of the study respondents were among those who has a college education, has bachelor degree and has a master's degree or higher [16].…”
Section: Literature Reviewsupporting
confidence: 63%
See 1 more Smart Citation
“…In a study conducted by Tscheulin and Lindenmeier, they found that the willingness to donate blood does increase with the level of education [15]. A consistent result also was found in a study conducted in the year 2006 that taken from Ahuja and Saluja whereby they found that 76% of the study respondents were among those who has a college education, has bachelor degree and has a master's degree or higher [16].…”
Section: Literature Reviewsupporting
confidence: 63%
“…However, that was in 1970s to 1980s. Later, it was found that, the average age was decreased and the willingness to donate blood will decline with the respondents' age [15]. Even, a more recent study conducted by Saluja's and Ahuja in tertiary care hospitals has indicated the same direction whereby they concluded that younger people had a high willingness to donate blood compared to the elders [16].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Posters and pamphlets at blood banks are probably more cost-effective than advertising in the mass media. In addition, blood donors are also often driven by altruistic or humanitarian motives (7).…”
Section: Discussionmentioning
confidence: 99%
“…Altruizam je bio najčešći motiv, što je i u saglasnosti sa brojnim studijama evropskih centara (14)(15)(16)(17). Tek 7.7% ispitanika bi krv darovalo zbog beneficija kao što su oslabađanje od participacije ili slobodni dani.…”
Section: Diskusijaunclassified